2013
DOI: 10.1159/000346763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Movement Music Therapy with the Naruko Clapper on Psychological, Physical and Physiological Indices among Elderly Females: A Randomized Controlled Trial

Abstract: Background: Recent interventional studies have indicated that some exercise programs have beneficial physical and immunological effects for older people. Some evidence suggests that exercise programs involving music and/or a rhythmic movement component may be particularly beneficial. Objective: To assess the effects of a new type of movement music therapy (MMT) on physical, immunological, hormonal and psychosocial health parameters among older adults. Methods: 112 elderly female subjects (average age 73.62 ± 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…MMT constitutes a multitask exercise program; subjects were required to shake the Naruko clapper instrument and singing a song at the time with the music, and simultaneously follow the body movement of a trainer. As subjects in the MMT group were required to pay attention to the timing of the Naruko throughout the exercise, MMT may have involved a higher level of cognitive performance than the control intervention involving a single physical task (Shimizu et al, 2013). Thus, the combination of rhythmic movement with cognitive functioning in our specific MMT intervention may have been necessary to activate the prefrontal area to the extent observed in the present study.…”
Section: Fab Scores and Frontal Lobe Activationmentioning
confidence: 74%
See 1 more Smart Citation
“…MMT constitutes a multitask exercise program; subjects were required to shake the Naruko clapper instrument and singing a song at the time with the music, and simultaneously follow the body movement of a trainer. As subjects in the MMT group were required to pay attention to the timing of the Naruko throughout the exercise, MMT may have involved a higher level of cognitive performance than the control intervention involving a single physical task (Shimizu et al, 2013). Thus, the combination of rhythmic movement with cognitive functioning in our specific MMT intervention may have been necessary to activate the prefrontal area to the extent observed in the present study.…”
Section: Fab Scores and Frontal Lobe Activationmentioning
confidence: 74%
“…Subjects were required to shake the Naruko clapper instrument and singing a song at the time with the music, and simultaneously follow the body movement of a trainer. This low-impact exercise simultaneously requires high levels of cognitive and motor function (Shimizu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Toda and Ichikawa [32] evaluated the consequence of watching a comedy video after performing a stress task (an arithmetic test), and found significantly higher salivary flow rates after watching the video but no influence on sCgA. Shimizu et al [45] did not observe significant variations in sCgA when assessing the effects of movement music intervention in female older adults. And, similarly, no effect of hand massage prompted relaxation was obtained in sCgA from female geriatric facility residents [46].…”
Section: Discussionmentioning
confidence: 98%
“…These isotypes -IgA, IgD, IgE, IgG and IgM -all have different heavy chains and thus exert different effect or functions (13). Exercise can cause a change in the consistency of serum Ig levels, among these changes are significant variations are in IgA, IgG and IgM (14). Numerous studies have shown that strenuous physical exercise leads to reduced serum IgA, IgG and IgM levels and as a result weakens the immune system.…”
Section: Effects Of Grb 1 On Serum Iga Igg and Igm Levels Of Ratsmentioning
confidence: 99%